Rheology in Fibre Formation for Meat-Analogues Data Analysis of Protein Melt Rheology Data (Annual Transactions of the Nordic Rheology Society, 2025)
Global meat consumption increased four-fold during the last fifty years, while population doubled1. Even if the increase in European meat consumption has slowed (currently 80 kg per capita, twice the world average), it is forecasted to increase by 10% more to 20302–4. The increase in meat eating is also nutritionally alarming as excessive consumption has been linked to health problems, such as coronary heart disease and certain cancers5.Fibrous, meat-like analogues are today commercially produced from soy, pea and wheat, utilizing an extruder to form a protein melt at high moisture content, high temperature and high pressure with subsequent active cooling on exit. A common denominator for the fibre formation in meat-analogues and plastics is that it is known how to produce the fibres but not exactly why they are formed. Consequently, it is still difficult to utilize the full potential of these techniques.The current hypothesis on the mechanisms responsible for the fibre formation contribute to understanding but are not sufficient to fully describe the formation and cannot be used to predict fibre formation ability of protein melts thus hampering the use of more sustainable protein sources. Overall, the hypotheses range from “physical”6–8, describing mechanisms in terms of fluid dynamics, heat transfer and phase separation, to “chemical” emphasizing the chemical interactions between protein chains or polymer crystallites.This contribution will focus on rheology of the protein melts, and especially on how to use state-of-the-art statistical analysis to determine the influence of temperature, protein and moisture content on rheological properties of the melts.